The End of an Era. the Recognition of Finland by Chile (1917-1919) [el Fin de Una Era. el Reconocimiento de Finlandia por Chile (1917-1919)] - Garay-Vera, C (Universidad de Alicante, 2021)
The establishment of diplomatic relations between Chile and Finland in 1918 was the product of the collapse of the Russian Empire and the dawn of the Bolshevik era. In the context of the Russian Civil War, Finland was recognized by the antagonistic parts of World War I, and Chile joined the considerations of Western powers that saw Finland’s split as an economic and political opportunity. This article singles out the role of Agustín Edwards McClure, then Chile’s ambassador to London, at the time when the foundations of the League of Nations and the new cast of nations emerging from the principle of self-determination are also beginning to be discussed, as was the case in Finland. © 2021 University of Alicante. All rights reserved.